Longitudinal Variation of the Lunar Tide in the Equatorial Electrojet. Issue 12 (11th December 2017) - Yamazaki, Yosuke; Stolle, Claudia; Matzka, Jürgen; Siddiqui, Tarique A.; Lühr, Hermann; Alken, Patrick
Abstract: The atmospheric lunar tide is one known source of ionospheric variability. The subject received renewed attention as recent studies found a link between stratospheric sudden warmings and amplified lunar tidal perturbations in the equatorial ionosphere. There is increasing evidence from ground observations that the lunar tidal influence on the ionosphere depends on longitude. We use magnetic field measurements from the CHAMP satellite during July 2000 to September 2010 and from the two Swarm satellites during November 2013 to February 2017 to determine, for the first time, the complete seasonal‐longitudinal climatology of the semidiurnal lunar tidal variation in the equatorial electrojet intensity. Significant longitudinal variability is found in the amplitude of the lunar tidal variation, while the longitudinal variability in the phase is small. The amplitude peaks in the Peruvian sector (∼285°E) during the Northern Hemisphere winter and equinoxes, and in the Brazilian sector (∼325°E) during the Northern Hemisphere summer. There are also local amplitude maxima at ∼55°E and ∼120°E. The longitudinal variation is partly due to the modulation of ionospheric conductivities by the inhomogeneous geomagnetic field. Another possible cause of the longitudinal variability is neutral wind forcing by nonmigrating lunar tides. A tidal spectrum analysis of the semidiurnal lunar tidal variation in the equatorial electrojet reveals the dominance of the westward propagating mode with zonal wave number 2 (SW2), with secondary contributions by westward propagating modes with zonal wave numbers 3 (SW3) and 4 (SW4). Eastward propagating waves are largely absent from the tidal spectrum. Further study will be required for the relative importance of ionospheric conductivities and nonmigrating lunar tides. Key Points: Complete seasonal‐longitudinal climatology is presented for the semidiurnal lunar tidal variation of the equatorial electrojet Significant longitudinal variation is found in the amplitude, while the variation in the phase is small Longitudinal variability can be partly explained by the effect of the inhomogeneous geomagnetic field